2020
DOI: 10.1108/ajim-10-2019-0290
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the use of YouTube as a learning resource: a social cognitive perspective

Abstract: PurposeDrawing from social cognitive theory, the purpose of this study is to examine how personal, environmental and behavioral factors can interplay to influence people's use of YouTube as a learning resource.Design/methodology/approachThis study proposed a conceptual model, which was then tested with data collected from a survey with 150 participants who had the experience of using YouTube for learning. The bootstrap method was employed to test the direct and mediation hypotheses in the model.FindingsThe res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 65 publications
4
53
0
1
Order By: Relevance
“…The convergent validity of measurement was satisfied based on the score of Average Variance Extracted (AVE) of between 0.886 and 0.914. [20] suggested that the AVE value above 0.50 indicated the satisfying level of convergent validity. The discriminant validity of measurement was also supported and based on the threshold value of Heterotrait-monotrait ratio (HTMT) below 0.90 (Hair et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The convergent validity of measurement was satisfied based on the score of Average Variance Extracted (AVE) of between 0.886 and 0.914. [20] suggested that the AVE value above 0.50 indicated the satisfying level of convergent validity. The discriminant validity of measurement was also supported and based on the threshold value of Heterotrait-monotrait ratio (HTMT) below 0.90 (Hair et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the findings, this study concluded that the user's acceptance of YouTube video as learning resources was related to three factors: perceived ease of use, perceived usefulness and social influence. Individual and environmental factors were both significant in the user's acceptance of YouTube for learning [20]. Perceived usefulness was an important factor for the anatomy students in Jordan, affecting their decisions to use YouTube as their learning resources [11].…”
Section: Discussionmentioning
confidence: 99%
“…Reference [38] stated that YouTube had positive contributions, especially in subjects they did not understand and students watched videos from YouTube as a substitute for textbooks. This referred to the importance of digital literacy from an early age-related to 21st-century skills [33]. Watching videos activated students' two different senses, seeing and hearing senses, and introduced them to the real things inside the videos [23], [6].…”
Section: Youtube Effect On Students' Learning Outcomes Satisfaction Self-improvementmentioning
confidence: 99%
“…Several studies confirmed that YouTube is one of the beneficial language learning teaching tools because it has various types of learning videos and is categorised as a rich source of teaching materials for young bilingual students [4], [11], [14], [7], [19], [16], [25], [20]. On the contrary, some studies found the complication and issues in implementing YouTube videos as learning resources in teaching English [34], [33]. Therefore, it is essential to examine social media's use in teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the adoption of information technology has identified that the social environment factors play significant influence in the adoption decisions (Venkatesh et al, 2003). Likewise, research on learning in social media has also emphasized the importance of the social environmental factors in influencing learners' attitude towards learning in such social platforms (Yu, Tian, Vogel, & Kwok, 2010;Q. Zhou, Lee, & Sin, 2016).…”
Section: Social Environmental Factorsmentioning
confidence: 99%